Organ donation and transplantation: a binomial to be optimized - Graf, Catarina Piolla; Silva, Orlando de Castro e (Medicina (Ribeirao Preto), 2017)
Over the years, organ transplantation has become a viable alternative for the treatment of end-stage diseases that, in the recent past, had high mortality rates. In this way, the number of people in the waiting list for organ transplantation has grown disproportionately to the number of organ donations, creating a gap that remains until now. In this article, we intend to discuss the issues that limit donation, especially family refusal, addressing the issue through the psychological bias of relatives at the time of death. In addition, we show updated numbers of donations and organ transplants in Brazil. Thus, it is concluded that an alternative to increase the donation rate is the instruction of the medical team that conducts the conversation with the relatives of the donor, as well as the awareness of the society, aiming at greater knowledge and understanding of the binomial donation and transplantation. Finally, it is discussed the project of the Academic League of Surgery and Transplantation of the FMRP- USP that, when promoting lectures in high schools, can induce discussions and solve possible doubts, in order to inform the young people about the reality of donations of organs and improve long-term donation rates.